Plasma Enhanced Chemical Vapor Deposited Materials and Organic Semiconductors in Photovoltaic Devices - A. Kosarev; I. Cosme; S. Mansurova; D. Andronikov; A. Abramov; I. Shakhray; Eu. Terukov (Известия высших учебных заведений России: Радиоэлектроника, 2020)
Introduction. PECVD enables fabrication of wide range of advanced materials with various structure such as amorphous, polymorphous, nano-crystalline, nanostructured, microcrystalline etc. and with various electronic properties. The latter can be also changed by different dopingl. PECVD silicon materials are commercially employed in multi-layered PV structures (including ones on flexible substrates). Combining these materials with crystalline silicon active substrate resulted in significant improvement of PCE in hetero junction technology PV structures. Existence of new organic semiconductors (OS) together with understanding of physical properties resulted in fast development of OC PV devicesAim. To consider both PECVD and OS materials and to present description of fabrication, structure and electronic properties for device application.Materials and methods. Devices based on non-crystalline materials, devices based on OS, hybrid devices. PECVD and Spin coating technique was used to deposit materials with tunable properties enabling device engineering possibilities.Results. PECVD and OS materials were analyzed. These materials have different levels of characterization (data volume, interpretation of the results etc.) and of understanding of physics determining device performance. Some examples of these materials in PV including structures with crystalline silicon were considered.Conclusion. Important advantage of both PECVD and OS materials is that fabrication methods are compatible and allow fabrication of great variety of hybrid device structures on crystalline semiconductors. Advantages of such devices are difficult to predict because of lack of data in scientific literature. However a new area in material science and related devices for further exploring and exploiting has appeared.